Evaluation of manufacturing feasibility and safety of an MDCK cell-based live attenuated influenza vaccine (LAIV) platform. Issue 52 (14th December 2020) - Ganguly, Milan; Yeolekar, Leena; Tyagi, Parikshit; Sagar, Umesh; Narale, Swapnil; Anaspure, Yashodhan; Tupe, Sham; Wadkar, Kuntinath; Ingle, Nilesh; Dhere, Rajeev; Scorza, Francesco B.; Mahmood, Kutub
Highlights: Suitability of MDCK cells for manufacturing of LAIV was established. High concentration of MDCK cells are required to induce tumors in SCID mice. MDCK cell lysate and extracted DNA was not oncogenic in three rodent species. Satisfactory virus growth was observed to support LAIV manufacturing. Abstract: Cell culture based live attenuated influenza vaccines (LAIV) as an alternative to egg-based LAIV have been explored because of lack of easy access to SPF eggs for large scale production. In this study, feasibility of MDCK platform was assessed by including multiple LAIV strains covering both type A (H1 and H3) and type B seasonal strains as well as the candidate pandemic potential strains like A/H5 and A/H7 for the growth in MDCK cells. A risk assessment study was conducted on the cell banks to evaluate safety concerns related to tumorigenicity with a regulatory perspective. Tumorigenic potential of the MDCK cells was evaluated in nude mice (10 7 cells/mouse) model system. The 50% tumor producing dose (TPD50 ) of MDCK cells was studied in SCID mice to determine the amount of cells required for induction of tumors. Further, we conducted an oncogenicity study in three sensitive rodent species as per the requirements specified in the WHO guidelines. We determined TPD50 value of 1.9 X 10 4 cells/mice through subcutaneous route. Our results suggest that, the intranasal route of administration of the cell culture based LAIV pose minimal to no risk of tumorigenicity associated with the host cells. Also, non-oncogenic nature of MDCK cells was demonstrated. Host cell DNA in the vaccine formulations was < 10 ng/dose which ensures vaccine safety. Production efficiency and consistency were characterized and the observed titer values of the viral harvest and the processed bulk were comparable to the expansion in embryonated eggs. The present study clearly establishes the suitability of MDCK cells as a substrate for the manufacture of a safe and viable LAIV.